THE TALE IN ANDALUSIAN SPEECHES: AN ANALYTICAL STUDY - M.L. /Dr. Mehdi Ali Mohamed Al-Mayali (American Journals Publishing, 2024)
This study addressed the story and how Arabs approach it and communicate it orally until it became a blog And this was the result of cultural diversity, multi-ethnicity and multiculturalism, all of which left its obvious effects on artistic prose. The books of stories and tales appeared down to the Andalusian speeches, which included in the most diverse tales that writers conveyed in a bright literary manner. In the Andalusian era, the stereotypical image overlaps with the sermon of the Andalusian era, so that the sermon is hardly without prejudice to the tale's style, This study is an attempt to clarify the ephemeral structure of the Ton of Andalusian speeches and journeys.
Keywords: Tale, narrative, Andalusian speeches, time, place.